A numerical and experimental study of micro-channel heat pipe solar photovoltaics thermal system. (15th November 2017) - Modjinou, Mawufemo; Ji, Jie; Li, Jing; Yuan, Weiqi; Zhou, Fan
Highlights: A novel photovoltaic/thermal system with micro-channel heat pipe was proposed. A detailed simulation model for the MHP-PV/T system was presented. Heat transfer limitations and transient study of the components have been analyzed. The hydrodynamic and vapor transient periods of the refrigerant was identified. The thermal and electrical efficiency of the MHP-PV/T has been calculated. Abstract: A novel micro-channel heat pipe array incorporated with crystalline silicon (c-Si) solar photovoltaic/thermal system (MHP-PV/T) was designed and constructed by the authors. The proposed design configuration combined c-Si solar cells and wide micro-channel heat pipes (MHP) that were filled with prescribed amount of acetone as refrigerant under a vacuum condition in the same insulated frame to simultaneously provide electrical and thermal energy. Heat and mass transfer characteristics of the MHP-PV/T were preliminary investigated using both numerical and experimental methods. The transient behavior and parametric heat transfer limitations of the heat pipe were also examined using MATLAB. A linear relation between the thermal instantaneous efficiency η th and the reduced temperature parameter ( T out - T in ) G T - 1 was established. The maximum instantaneous efficiency was found to be 54.0% with an electrical power output of 70 W. The results indicated that the daily thermal and electrical efficiencies were 50.7% and 7.6%, respectively. The transient behavior of the MHP shows a faster thermal response to heat input within the temperature range of 48.8–49.2 °C and slower response when the thermal diffusivity was reduced to 0.05 cm 2 /s. The results also reveal good agreements between model simulation and experimental measurement with sufficient confidence.